2011
DOI: 10.2136/sssaj2010.0360
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from an Irrigated Silt Loam Soil Amended with Anaerobically Digested Dairy Manure

Abstract: Dairy production in the Pacific Northwest has grown steadily during the past decade. This increase h.is been accompanied by management challenges associated with production of large concentrations of dairy animal wastes that are implicated in the decline in surface and subsurface water quality as well as an increase in the production of greenhouse gases (GHG). Field studies were conducted to characterize GHG emissions fi'om a silt loam soil planted to silage corn {Zea mays L.) amended with urea fertilizer (NPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Under similar conditions Collins et al (2011) reported little difference in C emissions from liquid manure-treated soils. By contrast, manure increased CO 2 emissions twofold when added to corn systems harvested for grain, which retained all corn stover residue in the field (Adviento-Borbe et al, 2010;Heller et al, 2010).…”
Section: Carbon Balancementioning
confidence: 82%
See 1 more Smart Citation
“…Under similar conditions Collins et al (2011) reported little difference in C emissions from liquid manure-treated soils. By contrast, manure increased CO 2 emissions twofold when added to corn systems harvested for grain, which retained all corn stover residue in the field (Adviento-Borbe et al, 2010;Heller et al, 2010).…”
Section: Carbon Balancementioning
confidence: 82%
“…Supplemental inorganic-N was not added to manure plots in 2009, but was included in 2010 and 2011 to meet yield targets. A control plot was not included in the gas emission study; however, because fertilizer and control soil treatments produce similar gas emissions (Collins et al, 2011), we assumed emissions for the two were identical in the current study.…”
Section: Gaseous Carbon Fluxesmentioning
confidence: 99%
“…The results of these studies do not allow an assessment of the effects of each of the single treatment steps on soil N 2 O emissions, as the difference to the control treatment comprises two sub-treatments, anaerobic digestion, and subsequent separation. As indicated previously, available data on N 2 O emissions after soil application of separated digestates indicated not only lower emissions after field application of the liquid fraction but also after field incorporation of the organic matter-rich solid residues Bertora et al 2008;Möller and Stinner 2009;Collins et al 2011). Currently, there is no explanation available for lower N 2 O emissions from each of the fractions after separation in comparison to an unseparated digestate.…”
Section: Impact Of Anaerobic Digestion On N 2 O Emissions From Field-mentioning
confidence: 86%
“…Agricultural soils that are a sink for CH 4 can become a source when organic material is applied. Collins et al (2011) found that CH 4 emissions after manure applications were higher than from unfertilized or fallow soil or when amended with urea or anaerobically digested fibre. Application of organic material will increase anaerobic micro-sites thereby stimulating emissions of CH 4 .…”
Section: Discussionmentioning
confidence: 91%